IMPLEMENTASI TRI HITA KARANA DALAM PELESTARIAN TRADISI BUDAYA MASYARAKAT LOKAL DI SAMSARA LIVING MUSEUM, DESA JUNGUTAN, KECAMATAN BEBANDEM, KABUPATEN KARANGASEM, BALI - Ida Ayu Karina Putri; Made Suardika Jaya (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2021)
ABSTRACTTourism is an important sector in Bali's development. The main capital used to attract tourists is the traditions and culture of the Balinese people which are based on Hinduism. Actualization of the application of Tri Hita Karana in the implementation of cultural tourism aims to direct the balance between tourism development and maintaining the ancestral tradition as found in the Samsara Living Museum. The purpose of this study was to determine the existing conditions and the application of Tri Hita Karana in the management of the Samsara Living Museum. This research technique used qualitative methods. The research was conducted by observation, interviews, and literature study. Data analysis technique was using descriptive qualitative. The results of this research showed ithat the Samsara Living Museum fulfills the main components of tourism products and has implemented Tri Hita Karana in its management.Keywords: cultural tourism, Tri Hita Karana, Karangasem, Bali